A study of the attitude and knowledge of teenagers in the Pietermaritzburg area towards contraception - Priya Israel; T Naidoo; M Titus (South African Medical Association, 2016)
Background. Preventing teenage pregnancy is an important means of improving adolescent health and reducing perinatal mortality.Objectives. To improve our understanding of teenagers’ attitudes towards and knowledge about contraception, access to contraceptionand sexual activity in our health district.Methods. A descriptive, cross-sectional, questionnaire-based study analysed demographic data, knowledge about, access to and use ofcontraceptives and knowledge about sexually transmitted infections (STIs) in teenagers from 13 to 17 years of age in seven schools in thePietermaritzburg area, KwaZulu-Natal, South Africa.Results. Of the 350 participants who answered the questionnaire completely, 24.9% reported being sexually active, of whom 70.1% usedcontraception. Knowledge about emergency contraception (EC) was generally poor (8.7%). Sexually active respondents were more awareof condoms (78.6% v. 56.9%), injectable contraception (57.4% v. 41.8%) and EC (14.6% v. 6.1%) than those who were not. Knowledgeabout STIs was generally good (71.7%) and improved with increasing grade at school. Males had a better understanding of condomsbeing protective against STIs than females (60.8% v. 39.4%).Conclusion. Knowledge about condoms and injectable and oral contraception is adequate, whereas that about EC and dualcontraception needs to be improved. Use of contraceptives other than condoms is poor, indicating a disparity between knowledge anduse.